A study on effect of soil-structure interaction on performance of strong-back structural system subjected to near and far-field earthquakes. (August 2021) - Taghizadeh, Mahdis; Gholhaki, Majid; Rezaifar, Omid
Abstract: During the past years, researchers have developed ideas to thoroughly investigate the behavior of structural bracing systems. Accordingly, one of these emerging systems is the Strong Back Bracing System by which the inter-story drifts are maintained constant to prevent the occurrence of failure. Hence, due to the importance of the soil-structure interaction (SSI) and the type of soil underlying the structure, the SSI needs to be taken into account for seismic-resistant design. Accordingly, this paper deals with the seismic behavior of the structures equipped with the Strong Back Bracing System considering the soil-structure interaction (SSI) under near and far-field earthquakes. In this respect, 3, 6 and 12-story structures resting on stiff and soft soil (soil type II and IV) have been analyzed. The results indicate that the ratio of the inter-story drift in the case of soft soil for all structures has increased by 11.67% under near-field records and subjected to the far-field motions, this ratio has raised by 7.7% for the 12-story building. Moreover, the ratio of the residual drift of the 3, 6, and 12-story structures under the average of near-field earthquakes, has decreased and increased by 8.52 and 36.02 in the case of stiff and soft soils, respectively.